Corrigendum: A relativistic theory of the field - Valenzuela, Mississippi (2022)
In writing out the eq. (36)  in my recent paper [1], an inadvertent error led to two errant numerical expressions in equations (37) and (38) that propagated to the “Field equations”. The main results and conclusions of my paper remain unchanged. All of the affected formulas are corrected below.